(untitled) (European Bison Conservation Newsletter, 2008)
The enclosure for bison breeding of the Institute of Applied Ecology is being planned in Grabin (commune: Bytnica, voivodship: lubuskie) on 30 ha seminatural fragment of a river valley with primeval landscape features. This terrain (meadow-swamp with fragments of mixed and alder forest) is unique as regards landscape features and its richness of fauna and flora. It also belongs to a disappearing group of landscapes, not only within the area of the voivodship, but also in the whole country. It is in the phase of indirect succession between natural and partially affected by humans, which is most desired in the natural environment. However, discarding the pasturing of animals in this area, where it has been carried out for hundred years, and the lack of complex protective actions, may lead to the further succession of shrubs and trees, and thereby to the disappearance of meadow-swamp vegetation. Abandonment of any actions within this area or intensive agricultural exploitation of this terrain will cause the depletion of the rich landscape as well as the present richness of its fauna and flora. Introduction of some European bison may help to stop further shrub-tree succession and, as a consequence, will contribute to the preservation of rare and endangered species of open areas which occur there in quite high numbers (e.g. orchids). The pasturing of animals in this fragment of valley will increase the number of insects, which entails the increase of other groups of animals, particularly the avifauna. Bison are supposed to supplement the seminatural landscape of the river valley which has become naturalized for a few dozens of years, and in which bison could be the primary occupants. It is assumed that a complex management of breeding in this terrain will not particularly affect the structure and dynamics of forests in this area. To what extent and with what result our assumptions will be realized will turn out in practice and can be proved by scientific studies.